HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN PERILAKU ISTRI DALAM DETEKSI DINI KANKER SERVIKS - Puspadewi, Gusti Agung Mas; Purnamayanti, Ni Made Dwi; Senjaya, Asep Arifin (Maternity and Neonatal : Jurnal Kebidanan, 2025)
Cervical cancer is a significant health concern for women, especially in developing countries, where it is a leading cause of mortality. Understanding the behavior of wives in detecting cervical cancer early is crucial in addressing this public health issue. This study aims to determine the relationship between knowledge level and husband's support with wife's behavior in early detection of cervical cancer in Negari Banjarangkan Village. This is a quantitative study using a cross-sectional approach. The sample size used was 153 people using the proportional sampling method. Data collection was done using questionnaires, and data analysis was performed using the Chi-square test. The test was conducted at a significance level of 5%. The results showed that the majority of the knowledge level about early detection of cervical cancer in Negari Banjarangkan Village in 2024 was in the moderately good category (75.8%). The majority of husband's support about early detection of cervical cancer in Negari Banjarangkan Village in 2024 was in the supportive category (50.3%). The majority of wife's behavior in early detection of cervical cancer in Negari Banjarangkan Village in 2024 was in the category of never doing early detection of cervical cancer (55.6%). Concluded there is a significant relationship between the level of knowledge and the wife's behavior in early detection of cervical cancer in Negari Banjarangkan Village in 2024.